Live birth in woman with premature ovarian insufficiency and 46, XY karyotype after chemotherapy and bone marrow transplant: a case report - Yaojia Zhang; Haiyan Wang; Xiaoqin Pan (BMC, 2023)
Abstract Background Premature ovarian insufficiency (POI) is a clinical syndrome defined by loss of ovarian function before the age of 40 years, characterized by elevated serum gonadotropin levels and decreased estrogen levels with menstrual disturbance. POI can be natural or iatrogenic such as after chemotherapy, radiotherapy and surgery. Case presentation In this study, we describe a successful live birth in a 31-year-old woman with POI and 46, XY Karyotype after being treated with chemotherapy and bone marrow transplant (BMT) for acute non-lymphocytic leukemia when she was 17 years old. With amenorrhea or oligomenorrhea for 11 years, her serum level of FSH was up to 35.0 IU/L and 53.0 IU/L taken 4 weeks apart, which can be diagnosed as POI. After controlled ovarian stimulation treatment for three cycles with different protocols and frozen-thawed embryo transfer (FET), she finally got a successful pregnancy and had a live birth later. Conclusions This case report serves as a reminder that karyotype of peripheral blood may mislead the diagnosis as disorders of sex development (DSD). It also demonstrates that it is possible for a woman with chemotherapy and bone marrow transplant induced POI can have successful pregnancy and live birth with appropriate therapy. Furthermore, as age may plays a predominant role in fertility rather than residual ovarian reserve, active treatment may be concerned for women with POI at younger age.